Geotechnical Properties and Microstructure of Lime-Fly Ash-Phosphogypsum-Stabilized Soil - Tebogo Pilgrene Mashifana; Felix Ndubisi Okonta; Freeman Ntuli (Advances in Civil Engineering)
The use of industrial waste as a potential stabilizer of marginal construction materials is cost effective. Phosphogypsum and fly ash are industrial wastes generated in very large quantities and readily available in South Africa. In order to explore the potential stabilization of vastly abundant expansive soil using larger quantity phosphogypsum waste as a potential modifier, composites with a mixture of lime-fly ash-phosphogypsum-basic oxygen furnace slag were developed. However because of the presence of radionuclide, it was necessary to treat the phosphogypsum waste with mild citric acid. The effect of the acid treatment on the geotechnical properties and microstructure of expansive soil stabilized with phosphogypsum-lime-fly ash-basic oxygen furnace slag (PG-LFA-BOF) paste was evaluated, in comparison with the untreated phosphogypsum. Expansive soil stabilized with acid-treated PG-LFA-BOF paste exhibited better geotechnical properties; in particular, the high strength mobilized was associated primarily with the formation of various calcium magnesium silicide and coating by calcium silicate hydrate and calcium aluminate hydrate. The soil microstructure was improved due to the formation of hydration products. The stabilized expansive soil met the specification for road subgrades and subbase. Stabilization of expansive soils with phosphogypsum, fly ash, and basic oxygen fly ash does not only improve engineering properties of soil but also provides a solution in relation to disposal and environmental pollution challenges.